Modeling, Synthesis and Fracture of Advanced Materials for Industrial and Medical Applications - Aizikovich, Sergei M.; Altenbach, Holm.; Eremeyev, Victor; Swain, Michael Vincent; Galybin, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book gathers papers presented at the international workshop PMSDAM$1 (B19. The respective contributions offer valuable insights for researchers working on numerical solutions to advanced materials problems. The problems concerning the remineralization of teeth are considered. Of particular interest are articles exploring topics at the interface of different disciplines.s
A Continual Model of Damage for Analyzing Long-Term Strength of Materials And Structural Elements -- Direct and Inverse Problems for Interface Crack Identification in Layered Media -- Experimental and Clinical Investigation of Carbon Nanostructural Material for Orthopedic Applications -- In Vitro Degradation Test of gd, Si- Substituted Hydroxyapatite -- Deformation and Fracture of Titanium Alloys under Dynamic Loading -- Experimental and Theoretical Solution of the Problem on the Generating of Fatigue Wear in Heterogeneous Materials and Coatings -- The Method of Elastotonometry for Cornea Weakening in the Peripheral Annual Zone -- Nanoindentation Derived Mechanical Properties of Human Enamel and Dentine Subjected to Etching with Different Concentration of Citric Acid -- Interface Frictional Behaviour of Aluminium and Iron Powder Compacts at Room Temperature -- The Efficiency of Re-Dental Orthopedic Treatment of Patients with Extensive Dentition Defects due to the Flexibility of the Bases of Remov-Able Dentures and Optimization of their Attachment.
Keywords: Biomaterials; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Nanotechnology; Biomaterials; Engineering Thermodynamics, Heat and Mass Transfer; Nanotechnology